Growth option for a traditional SME in the food and beverage industry – A case of Loke Kee biscuits - Fong, Pui Mun (2025)
Loke Kee is a well-established Malaysia small and medium-sized enterprise (SME) with a rich history spanning over 77 years since its inception in 1947. Renowned for its expertise in producing traditional Chinese cookies, LK has established a reputation for its superior product quality and unwavering commitment to excellence. To ensure the safety and integrity of the product, LK’s manufacturing facility is certified by Halal Jakim and has attained food safety qualification such as Food Safety Management System (FSSC) 22000 and Hazard analysis and critical control point (HACCP). These certifications have solidified the company’s market position by demonstrating its commitment to quality and compliance.